Glutathione Peroxidase 1 Protects Against Peroxynitrite-Induced Spiral Ganglion Neuron Damage Through Attenuating NF-κB Pathway Activation - Wang, Xue; Han, Yuechen; Chen, Fang; Wang, Man; Xiao, Yun; Wang, Haibo; Xu, Lei; Liu, Wenwen (Frontiers in Cellular Neuroscience, 2022)
Glutathione peroxidase 1 (GPX1) is a crucial antioxidant enzyme prevented the harmful accumulation of intra-cellular hydrogen peroxide. GPX1 might contribute to limiting cochlear damages associated with aging or acoustic overexposure, but the function of GPX1 in the inner ear remains unclear. The present study was designed to investigate the effect of GPX1 on cochlear spiral ganglion neurons (SGNs) against oxidative stress induced by peroxynitrite, a versatile oxidant generated by the reaction of superoxide anion and nitric oxide. Here, we first found that the expression of GPX1 in cultured SGNs was down-regulated after peroxynitrite exposure. Then, the GPX1 mimic ebselen and the gpx1 knockout (gpx1-/-) mice were used to investigate the role of GPX1 in SGNs treated with peroxynitrite. The pretreatment with ebselen significantly increased the survived SGN numbers, inhibited the apoptosis and enhanced the expression of 4-HNE in cultured SGNs of peroxynitrite + ebselen group compared to the peroxynitrite-only group. On the contrary, remarkably less survived SGNs, more apoptotic SGNs and higher expression level of 4-HNE were detected in peroxynitrite + gpx1-/- group compared to peroxynitrite-only group. Furthermore, rescue experiments with antioxidant N-acetylcysteine (NAC) showed that the expression of 4-HNE and the apoptosis in SGNs were significantly decreased, while the number of surviving SGNs was increased in peroxynitrite + NAC group compared to peroxynitrite-only group as well as in peroxynitrite + gpx1-/- + NAC group versus peroxynitrite + gpx1-/- group. Finally, mechanistic studies showed that the activation of nuclear factor-kappa B (NF-κB) was involved in the SGNs damage caused by peroxynitrite and that GPX1 protected SGNs against peroxynitrite-induced damage, at least in part, via blocking the NF-κB pathway activation. Collectively, our findings suggest that GPX1 might serve as a new target for the prevention of nitrogen radical-induced SGNs damage and hearing loss.